Chemometric optimization of online SPE-LC method using polypyrrole-graphene oxide sorbent for tetracycline analysis in water samples - Zaini, Nurzaimah; Jawad, Ali H.; Mohamad Hanapi, Nor Suhaila; Yahaya, Noorfatimah; Anis, Ahmad Lutfi; Kamaruzaman, Sazlinda; Wan Ibrahim, Wan Nazihah (Walailak University, 2025)
A novel automated analytical method integrating online solid-phase extraction with liquid chromatography (online-SPE-LC) with chemometrically optimization was developed for the rapid and sensitive quantification of five selected tetracycline antibiotics, namely oxytetracycline, tetracycline, demeclocycline, chlortetracycline and doxycycline in water samples. In this method, a green polypyrrole-graphene oxide (PPy-GO) composite was employed as extraction sorbent. The effects of flow rate, valve switching time, sorbent mass, solvent composition and buffer pH were investigated using half-fraction Central Composite Design (CCD) of Response Surface Methodology (RSM). Optimal conditions were determined to be a solvent flow rate of 0.75 mL min⁻¹, valve switching time of 1.6 min, sorbent mass of 55 mg, solvent composition of 80:20 (ACN:water), and buffer pH of 2.5. The optimized method exhibited excellent linearity (R2 = 0.9990-0.9997) across a wide concentration range (10-1000 µg L−1) with low limits of detection (3.2-6.7 µg L−1). Method precision and accuracy were demonstrated by recoveries ranging from 82%-102% and relative standard deviations (RSDs) of 0.6%-3.0% (n=3) in both river and tap water samples. Compared to existing approaches, the developed method shows superior selectivity, high sensitivity, rapid and automation. Thus, this study highlights the great potential of PPy-GO as efficient sorbent integrated with online-SPE-LC method for the extraction of tetracycline from water samples.